2014
DOI: 10.14434/pders.v33i2.5186
|View full text |Cite
|
Sign up to set email alerts
|

Eight Steps to School-Based Employment Training for Adolescents with Autism Spectrum Disorder and Intellectual Disability

Abstract: Despite the transition requirements mandated by IDEA, and a growing body of research supporting effective transition planning for learners with autism spectrum disorders and intellectual disability, current national surveys of transition from school to work document dismal employment outcomes for adults with significant disabilities who frequently are without employment or are underemployed. Enrollment in vocational or employment-related programs in high school improves post-secondary employment attainment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 52 publications
0
11
0
8
Order By: Relevance
“…Nous avons retenu dix articles empiriques sur le sujet de la formation professionnelle et de l'intégration à l'emploi des personnes présentant une DI, dont un seulement en français (Hart Barnett et Crippen, 2014;Carroll, Blumberg et Petroff, 2008;Dolyniuk, et collab., 2002;Dumais, Prohet et Archambault, 2012;Grigal, Hart et Migliore, 2011;Hall, Kleinert et Kearns, 2000;Judge et Gasset, 2015;Kleinert, et collab., 2012;Mautz, Storey et Certo, 2001;Weir, 2004).…”
Section: Résultatsunclassified
See 2 more Smart Citations
“…Nous avons retenu dix articles empiriques sur le sujet de la formation professionnelle et de l'intégration à l'emploi des personnes présentant une DI, dont un seulement en français (Hart Barnett et Crippen, 2014;Carroll, Blumberg et Petroff, 2008;Dolyniuk, et collab., 2002;Dumais, Prohet et Archambault, 2012;Grigal, Hart et Migliore, 2011;Hall, Kleinert et Kearns, 2000;Judge et Gasset, 2015;Kleinert, et collab., 2012;Mautz, Storey et Certo, 2001;Weir, 2004).…”
Section: Résultatsunclassified
“…De façon générale, les écrits servent à souligner le rôle clé des institutions postsecondaires, telles que les collèges et les universités, dans l'acquisition des habiletés interpersonnelles et professionnelles nécessaires à l'intégration à un emploi des personnes présentant une DI (Grigal, Hart et Migliore, 2011;Hart Barnett et Crippen, 2014;Kleinert, et collab., 2012;Carroll, Blumberg et Petroff, 2008;Dolyniuk, et collab., 2002;Hall, Kleinert et Kearns, 2000). La recherche dans le domaine de la formation professionnelle invite aussi les institutions à privilégier une approche individualisée et centrée sur la personne (Judge et Gasset, 2015;Dumais, Prohet et Archambault, 2012;Kleinert, et collab., 2012;Carroll, Blumberg et Petroff, 2008;Weir, 2004;Dolyniuk, et collab., 2002).…”
Section: Résultatsunclassified
See 1 more Smart Citation
“…Adolescents with a high degree of autism are less likely to participate in various physical exercises, teambased activities, or club activities. Barnett & Crippen (2014) stated that the life satisfaction of children with autism is significantly lower than that of children without autism. Thus, a high degree of autism results in low life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the National Center for the Study of Postsecondary Educational Supports, students with disabilities reported an overall fear of transition, specifically with regard to employment (Stodden, ). Despite the enactment of Workforce Innovation and Opportunity Act () and its one‐stop centers providing coordinated, high‐quality support to job‐seekers, the majority of people with ID continue to experience higher rates of unemployment and underemployment compared with typically developing peers despite research documenting the employability of the ID population (Butterworth et al, ; Hart Barnett, & Crippen, ; Migliore & Domin, ; Winn & Hay, ). Young adults with ID also make less money per hour than their neurotypical peers (Cameto et al, ; Jennes‐Coussens, Magill‐Evans, & Koning, ) and peers with disabilities ($7.90 vs. $10.70–11; Newman et al, ).…”
Section: Introductionmentioning
confidence: 99%